Specificity of arrestin subtypes in regulating airway smooth muscle G protein‐coupled receptor signaling and function. Issue 10 (23rd June 2015) - Pera, Tonio; Hegde, Akhil; Deshpande, Deepak A.; Morgan, Sarah J.; Tiegs, Brian C.; Theriot, Barbara S.; Choi, Yeon H.; Walker, Julia K. L.; Penn, Raymond B.
ABSTRACT: Arrestins have been shown to regulate numerous G protein‐coupled receptors (GPCRs) in studies employing receptor/arrestin overexpression in artificial cell systems. Which arrestin isoforms regulate which GPCRs in primary cell types is poorly understood. We sought to determine the effect of β‐arrestin‐1 or β‐arrestin‐2 inhibition or gene ablation on signaling and function of multiple GPCRs endogenously expressed in airway smooth muscle (ASM). In vitro [second messenger (calcium, cAMP generation)], ex vivo (ASM tension generation in suspended airway), and in vivo (invasive airway resistance) analyses were performed on human ASM cells and murine airways/whole animal subject to β‐arrestin‐1 or ‐2 knockdown or knockout (KO). In both human and murine model systems, knockdown or KO of β‐arrestin‐2 relative to control missense small interfering RNA or wild‐type mice selectively increased (40‐60%) β2‐adrenoceptor signaling and function. β‐arrestin‐1 knockdown or KO had no effect on signaling and function of β2‐adrenoceptor or numerous procontractile GPCRs, but selectively inhibited M3 muscarinic acetylcholine receptor signaling (∼50%) and function (∼25% ex vivo, >50% in vivo ) without affecting EC50 values. Arrestin subtypes differentially regulate ASM GPCRs and β‐arrestin‐1 inhibition represents a novel approach to managing bronchospasm in obstructive lung diseases.—Pera, T., Hegde, A., Deshpande, D. A., Morgan, S. J., Tiegs, B. C., Theriot, B. S., Choi, Y. H., Walker, J. K. L., Penn, R. B. Specificity of arrestin subtypes in regulating airway smooth muscle G protein‐coupled receptor signaling and function. FASEB J. 29, 4227‐4235 (2015). www.fasebj.org